Informing the policymaking landscape: From research to action in the fight against climate change and hunger - De Pinto, Alessandro (2016)
Alex De Pinto Global Landscapes Forum IFPRI Session: Informing the policymaking landscape: From research to action in the fight against climate change and hunger Marrakech, Morocco November 16, 2016